Sefer Yeṣirah and its contexts : other Jewish voices - Weiss, Tzahi (Divinations., 2018)
In ""Sefer Yeṣirah"" and Its Contexts, Tzahi Weiss explores anew the contested history of Sefer Yeṣirah, in the process extending our knowledge of Jewish intellectual traditions excluded from rabbinic canon.